Professional Training of the First Grades Teacher as a Space for Competence Development (Nauczyciel wczesnej edukacji: Rozwijanie kompetencji zawodowych, 2016)
The paper takes up the problem of the professional training of first grades teachers. Three aspects of the problem are considered: the professional start and adjustment to the profession, the professional development as well as shaping of professional competence. The author challenges a thesis saying that the professional training it is a consecutive educational stage in the professional development of teachers and it requires strategic improvements and changes in its curriculum. Next the author presents some example solutions in this field.